NADH:ubiquinone reductase activity in kidneys of rats under different nutrition supplies. - Ursatyi, Mariya; Voloshchuk, Oksana; Kopylchuk, Galina (My University, 2021)
The issue of food security is one of the main global problems of mankind, as malnutrition is considered to be one of the determining factors in the development of a number of metabolic disorders. The question of the mechanisms of formation of metabolic disorders in the kidneys under conditions of nutritional imbalance has become especially relevant. The functional activity of the kidneys is largely determined by the efficiency of the energy supply system.
Keywords: нутрієнти; мітохондрії